SURVIVAL OF DIFFERENT BACTERIAL SPECIES ON DIFFERENT INANIMATE SURFACES STORED AT DIFFERENT CONDITIONS: (I) SURVIVAL OF Escherichia coli ON VARIOUS SOLID SURFACES STORED AT TWO TEMPERATURES. - S.R. AL-Obaidi , A. (The Iraqi Journal of Veterinary Medicine, 1994)
Survival of E. coli (0114:K90) on each of glass, wood, polystyrene and metal surfaces surfaces was studied. Artificially contaminated contaminated surfaces were stored at both 4°C and room temperature (18-20°C), and samples from cach surface were collected approximately after 1, 3, 10 and 40 40 days of storage, and cultured for bacterial growth. E. coli was recovered from glass and polystyrene surfaces after 1, 3 and 10 days of storage at both temperatures; from wood up till 40 days of storage at both temperatures; but the only exception was metal surface, where the organism was recovered only after 1 and 3 days of storage at room temperature, but was not isolated from the same surface stored at 4°C